Tecnologia cuidativo-educacional para promoção da autonomia de famílias de crianças com gastrostomia - CALDAS, Ana Caroline Silva (2017)
The making of gastrostomy leads many families to experience conflicting moments characterized by uncertainty, stress and disagreements between parents. In addition to the feelings of anguish and fear unveiled by caregivers, families are required to have innumerable knowledge and practices that are unusual for the daily care of children. Families need to receive professional support and have the social support network to deal with adversities that permeate family life. This research seeks to develop educational-care technology to support the care of the gastrostomy child based on the Model of Interpersonal Relations of Peplau and conception of Autonomy of Paulo Freire. Qualitative descriptive research utilized the Sensitive Creative Method (MSC) and Body Knowledge dynamics. Participants were 10 families living the gastrostomy preparation process, from the preoperative to the home care. For data collection, we used semi-structured interview recorded in audio, systematic observation and field notes. The data were coded / recoded and the situations-problems revealed were substrate for construction of the educational-care technology. The situation-problems encountered were: lack of knowledge of the families about the hospitalization process of the child, difficulty in the families' perception on gastrostomy, disruption of the parents' ideal of a perfect child, insufficient health education to attend to the demands of family care for the children with gastrostomy, resignation to the new family situation, having a child dependent on technologies, loss of the physiological feeding route. It is concluded that families with knowledge about gastrostomy will be empowered with their rights and thus may transform their reality. The technology can help families better understand what a gastrostomy is and how to handle it so that the care safely provided to the child helps in adapting to the situation of chronicity experienced.